Mandarin phrasebook & dictionary - Garnaut, Anthony; Lu, Tim (Lonely Planet, 2015)
This phrasebook provides comprehensive mix of practical and social words and phrases. -- Chat with the locals and discover their culture. --Order the right meal with our menu decoder. --Never get stuck for words with our 3500-word two-way dictionary. --With shortcuts, key phrases & common Q & As. --Feel at ease, with essential tips on culture & manners. Coverage includes: Basic language tools such as pronunciation; phrases for getting out and about, being social, food, safe travel, sustainable travel, and more; and two dictionaries